Estudos de adsorção de tetraciclina e cromoglicato em partículas de quitosana - Lima, Camila Renata Machado de (2013)
Among the polymers that stand out most in recent decades, chitosan, a biopolymer with physico-chemical and biological promising properties has been the subject of a broad field of research. Chitosan comes as a great choice in the field of adsorption, due to their adsorbents properties, low cost and abundance. The presence of amino groups in its chain govern the majority of their properties and define which application a sample of chitosan may be used, so it is essential to determine their average degree of deacetylation. In this work we developed kinetic and equilibrium studies to monitor and characterize the adsorption process of two drugs, tetracycline hydrochloride and sodium cromoglycate, in chitosan particles. Kinetic models and the adsorption isotherms were applied to the experimental data. For both studies, the zeta potential analyzes were also performed. The adsorption of each drug showed distinct aspects. Through the studies developed in this work was possible to describe a kinetic model for the adsorption of tetracycline on chitosan particles, thus demonstrating that it can be described by two kinetics of adsorption, one for protonated tetracycline and another one for unprotonated tetracycline. In the adsorption of sodium cromoglycate on chitosan particles, equilibrium studies were developed at different temperatures, allowing the determination of thermodynamic parameters